Literature Review: Edge Computing and Its Role in the 5G Era - Julinaldi, Julinaldi (MSJ : Majority Science Journal, 2025)
This literature review examines the strategic role of edge computing in supporting technological advancements in the 5G era. As a distributed computing architecture that places data processing closer to its source, edge computing is considered effective in reducing latency, minimizing network load, and enabling real-time decision-making. Through an analysis of empirical findings, conceptual frameworks, and recent technological developments, this study explores the integration of edge computing within the Internet of Things, industrial automation, and various intelligent systems. The findings highlight the contribution of edge computing to strengthening responsive and scalable digital infrastructure capable of handling large-scale data flows in 5G networks. The review also identifies several key challenges, including data security issues, device interoperability, and the need for efficient computing resource management. Existing studies emphasize the importance of technological innovations such as improved device orchestration mechanisms and more effective load distribution algorithms to optimize edge performance. The integration of edge computing with cloud computing and artificial intelligence is viewed as a future development direction that can enhance the resilience and flexibility of digital ecosystems. Overall, this review confirms that edge computing plays a significant role in shaping a modern computing environment that is faster, more secure, and more adaptive to the demands of digital transformation in the 5G era.